Menuju Koperasi Modern: Sebuah Upaya Transformasi Digital Koperasi Mahasiswa Pendidikan Ekonomi Kota Kendari - Muhammad Syaiful; Sapriyadi Sapriyadi; Erytnanda Akbar; Turis Turis (Universitas Batanghari, 2022)
In this era that is very close to technology, cooperatives are faced with 3 major challenges that need to be answered, namely bad perceptions of cooperatives, innovation of cooperative business systems, and technological developments. The demand to change the conventional system into an all-digital system is unavoidable so that digital transformation is very necessary, especially in the service sector to consumers in order to make it easier for consumers to transact. The economic education student cooperative in the city of Kendari has been operating for 10 years but still seems to have not maximized technology in the development of the cooperative. In this student cooperative, there are still many things that become obstacles in its implementation, such as member participation that has not been maximized, both contributory participation and incentive participation. The specific purpose of this research is to find out how the cooperative transformation efforts are carried out by the economic education student cooperative in an effort to increase member participation and also to determine the role of the government in efforts to modernize cooperatives. Data collection methods in this study were obtained in 3 ways, namely observation of the research location, interviews with informants, and literature study. The conclusion of this research reveals that several efforts have been made by student cooperatives for economic education to become modern cooperatives, namely using the Zoom application for the Annual Members Meeting (RAT) and developing their own applications to make it easier for members to buy goods and services and facilitate deposit payments.. Meanwhile, the government's efforts are to provide socialization, training, and create a digital platform that can be used by cooperatives.